Financial infrastructure—total factor productivity (TFP) nexus within the purview of FDI outflow, trade openness, innovation, human capital and institutional quality: Evidence from BRICS economies. Issue 7 (7th February 2023) - Rehman, Faheem Ur; Islam, Md Monirul
ABSTRACT: BRICS countries' contribution to the global economy has received wider attention. The critical factor behind their role is financial market reform that stimulates these economies' productivity growth. This research contributes to constructing a comprehensive index of financial infrastructure and measuring its relationship with BRICS economies' total factor productivity (TFP) within the purview of outward FDI, trade openness, human capital, innovation and institutional quality during 1990–2019 using the CS-ARDL technique. The findings divulge a significant and positive role of financial infrastructure in TFP both in the long and short runs, while outward FDI, trade openness, human capital, and innovation walk on the same footing in BRICS countries. Moreover, the CS-ARDL-based investigated findings remain the same across the two-way fixed effect with Driscoll and Kraay Standard Error technique. Therefore, BRICS countries' more promotion of financial dynamics and other ancillary economic, demographic, and technological factors is critical to stepping towards the spectacular growth trajectory.